Oxford advanced learner's dictionary - Wehmeier, Sally (Oxford University Press, 2005)
This is the world's bestselling advanced learner's dictionary, recommended by learners of English and their teachers, and used by 30 million people.brbr NEW 32-page Oxford 3000and#8482; Vocabulary Trainer, only available with the Paperback and CD-ROM edition.